Brand Recall on Indomie's Tagline "Seleraku" (Semiotic Analysis of Roland Barthes on Indomie's Tagline) - Andary, Ria Wuri; Tamsil, Ilma Saakinah (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
Brand recall plays a crucial role in building a strong relationship between consumers and brands. One important aspect of brand recall is the use of a tagline, which aims to create a lasting impression and strengthen brand recall. This study delves deeper into the power of the tagline "Seleraku" in building brand recall for Indomie products. Using Roland Barthes' semiotic approach, this research analyzes the deeper meaning behind the tagline. The findings show that the tagline "Seleraku" not only refers to taste but also creates a strong emotional connection between consumers and the Indomie brand. Through an analysis of advertisement content, it was found that the consistent use of visuals and text reinforces the connotative meaning of the tagline, such as pride in being a local product and personal attachment. This connotative meaning plays a significant role in shaping consumer memory of the Indomie brand. Furthermore, the study also found that the consistency of the tagline’s use across various advertising media contributed to Indomie's success in creating high brand awareness. Therefore, it can be concluded that the tagline "Seleraku" is a key factor in Indomie's success in building customer loyalty and maintaining its dominant position in the instant noodle market. This study contributes to a deeper understanding of the role of semiotics in marketing communication, particularly in the context of building brand recall.